Sustainability of Corn Farming Systems on Post-Sand Mining Land in Malang, East Java, Indonesia - Khusni, Ahmad; Suhartini, Suhartini; Sujarwo, Sujarwo (Department of Social Economy, Faculty of Agriculture , University of Brawijaya, 2024)
The sand mining activities leave a wide area ex-sand mining land. In Bambang Village, farmers who live in that area try to get their land back to produce agricultural activities that were used previously for sand mining. However, there are several obstacles to the sustainability of farming in this area, especially the matter of critical land issues, pest and disease attacks, unpredictability of price, and technology used still not optimized suboptimal use of technology. To analyze the sustainability index and the attributes that influence continuity of corn farming on post-mine sand land, a quantitative study was conducted used a five-dimension sustainability approach. This approach included the consist of ecological, economic, social, institutional, and technological dimensions. Data collected by distributing questionnaires to the respondents which are divided into 72 of farmers and five key informants, so that, total of respondents are 77 people. Multidimensional Scaling (MDS) and leverage analysis were used to determine the attributes that influence sustainability. The results of the research show corn farming continuity on post-sand mining land produce a sustainability index for about 54.86%. It is considered quite able to maintain in terms of the economic dimension (62.12%), social dimension (60.82%), and institutional dimension (60.27%). Though, the ecological dimension (46.88%) and technological dimension (44.23%) were classified as weak in terms of sustainability. Additionally, leverage analysis shows about 25 sensitive attributes which is influenced the sustainability of corn farming on post-sand mining land.